Ренесансні топоси і мотиви у джестовій збірці «Торбина новин» (1558): специфіка інтерпретації та аксіологічна семантика - Козьмик, Г. (Інститут літератури ім. Т.Г.Шевченка НАН України, 2009)
Статья посвящена выявлению специфики интерпретации ренессансных топосов и мотивов в джестах анонимного сборника „Котомка новостей” (1558). Анализ английских ренессансных джестов, осуществляемый сквозь призму методологи „нового историзма”, позволяет воспроизвести общую социально-психологическую атмосферу того периода, пролить свет на некоторые важные особенности национальной ментальности и юмора. The research deals with the peculiarities of the Renaissance topoi and motifs interpretation in the jests from the anonymous collection “The Sackful of News” (1558). The article is concentrated on jests analysis through the prism of New Historicism, which allows reconstructing the general social and psychological atmosphere of that period, revealing some essential features of the national mentality and humour.